THE ISSUE OF SUBSTITUTION RELATED TO NONVERBAL MEANS OF COMMUNICATION IN TRANSLATION OF LITERARY TEXTS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The problem of substituting lexis used to represent nonverbal communication means in translation is a complex issue that arises from the challenges of conveying nonverbal cues across different languages and cultures. As we know, nonverbal communication includes gestures, facial expressions, body language, and other forms of nonverbal behavior that are integral to conveying meaning in both verbal and nonverbal forms. When translating literary texts, these nonverbal elements can pose significant challenges due to differences in cultural norms, linguistic expressions, and contextual understanding. Here’s a detailed look at the problem: